Pendistribusian Data Rekam Medis Elektronik Antar Klaster melalui Sistem e-Puskesmas di Puskesmas X Banjarmasin: Distrubtion of Electronic Medical Record Data Between Clusters Through The E-Puskesmas System at Puskemas X Banjarmasin - Eka Rahma Ningsih; Nirma Yunita (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Digital transformation in the health sector encourages every healthcare facility to manage medical record data electronically, in an integrated and real-time manner. One of the key implementations is the e-Puskesmas system, which functions to automatically manage patient data, services, and health reporting. This study aims to analyze the distribution flow of electronic medical record (EMR) data across service clusters through the e-Puskesmas system at Puskesmas X, as well as to identify its effectiveness and the technical challenges in its implementation.This research employed a qualitative approach with an exploratory case study design. Data were collected through observations, in-depth interviews with registration officers, medical staff, and IT personnel, and document analysis of SOPs and system activity logs.The results indicate that the distribution process of EMR data at Puskesmas X operates automatically and is fully integrated across service clusters using the e-Puskesmas system, covering patient registration, data entry, inter-cluster distribution, recording of medical services, and automatic synchronization with the Banjarmasin City Health Office server. This process improves efficiency, data accuracy, and the continuity of patient information. However, several challenges remain, including internet instability, data input errors, limited IT personnel, and reliance on manual entry. In conclusion, the e-Puskesmas implementation at Puskesmas X has proven effective and supports Indonesia’s national Satu Sehat Platform for digital health transformation.